Membangun Positive Brand Tentang Minuman Toak Produksi Warga Desa Hendrosari Kabupaten Gresik - Moch Mottaman; Abdiel Alfan Karuniawan; Chudaifah Al Syahlan; Puasini Aprilyantini (LPPM Stikosa - AWS, 2021)
The existences of traditional drink, Toak, is in stagnant condition and have less enthusiasts because of the wrong perception in the public about this traditional drink that made from the essence fermentation of siwalan fruit. Meanwhile, Sake, a traditional drink contains of alcohol from Japan that always serves in every traditional ceremony such as traditional wedding in Japan which is symbolizes unity / forming a new bound (source: jejakpena.wordpress.com). Because of those reasons, the writer conducted a research about how negative cognition which is cling on Toak produces by the villagers of Hendrosari, Gresik District turned into positive cognition because its effect can make the body of human warmed or refreshed. This research uses qualitative descriptive method such as, observation, data collection, and interview in order to found the distortion and also the solution by using “Cognitive Disonative” theory by Keon Festinger. The purpose of this research is to educating the tappers and Toak merchant, and also to suggests the Government of Gresik District to make Toak become an iconic product which is serves to the guest / visitor of the District of Gresik. The result is to build a positive cognition by branding the image of Toak as a traditional drink even though in the middle of Covid-19 pandemy by using digital marketing (Instagram), socialize a traditional drink in a package of bottle glass with a “Nosari” logo, complete with the information of traditional drink benefit and its contents along with the serving method so the drink can be enjoy by guest, visitor, or tourist.